Curating architectural collections : Interaction with immersive stereoscopic visualisation - Datta, S.; Chang, T.; Hollick, J (2016)
We present our research on the use of immersive stereoscopic visualisation in interaction with collections of architectural representations. We investigate the processing and visualisation of multiple model representations from architectural datasets. We develop two models for locating collections of datasets in spatial contexts, namely a realistic gallery and a synthetic landscape. We evaluate and report the qualitative interactive experience with two forms of contextual interaction within a novel stereoscopic immersive visualisation (cylindrical projection) environment. The use of immersive stereoscopic visualisation conveys aspects and dimensions of the collections that would not be possible without the forms of contextual interaction, the gallery metaphor and the synthetic landscape to interact with the architectural collections. The combination of abstract representations with realistic sense of scale and interaction provide the user with an immersive experience to convey the collective form.